The effect of different consumption rates of the herbicide Harmony 75, VG on the level of stress in soybean plants - Storchous, I.; Ivaschenko, O. (Quarantine and plant protection, 2022)
Goal. To establish the optimally high efficiency of weed control in soybean crops with a two-time application of the herbicide Harmony 75, VG to relieve stress in crop plants. Methods. Field, laboratory, quantitative-weighing, visual, calculation-comparative, mathematical-statistical. Results. It was established that a one-time spraying of crops with the herbicide Harmony 75, VG with the maximum consumption rate from the recommended (8.0 g/ ha) could be one of the factors that induced stress in soybean plants, delaying the intensity of photosynthesis and partially inhibiting other physiological processes (chlorophyll content a and b 5 days after spraying decreased (0.8 g/ dm2) compared to the data obtained before spraying (0.9 g/ dm2)). Research has established that two-time spraying of crops with the herbicide Harmony 75, VG at a rate of 5.0 g/ ha, the first — during the phase of the first triple leaf in soybean plants, the second — on the 4th day after the first, with observance of the time interval, ensured seedling control weeds and restrained the formation of vegetative mass, the average indicator of which was significantly lower compared to the average indicator established in the plots of the control version of the experiment, and was 15.7% of it. According to the results of the research, the average seed yield was the closest in value to the average yield of soybean seeds, which was obtained in the control plots of crops, where 4 consecutive manual weeding of crops was carried out during the growing season and the segetal vegetation was completely destroyed (3.31 t/ ha or 91.2%), recorded on the plots of crops with a two-time treatment of Harmony 75, VG with a rate of consumption of 5.0 g/ ha + 200 ml/ ha of PAR Trend 90 (the first treatment during the phase of the first triple leaf in soybean plants, the second treatment at 4 — that day after one). Conclusions. Two-time spraying with the herbicide Harmony 75, VG, with a rate of consumption of 5.0 g/ ha + 200 ml/ ha of surfactant Trend 90 (the first time — during the phase of the first triple leaf in soybean plants and the second time — on the 4th day after the first) makes it possible to control the emergence of weeds, restrain the formation of vegetative mass, causes reduced stress in crop plants compared to a one-time introduction of the recommended rate, and ensures a higher yield of soybean seeds.